Resolution of Disputes Regarding Missing Balances without Transactions on the Dana App - Alya Deska Safira; Sri Handayani; Helena Primadianti S (Repertorium: Jurnal Ilmiah Hukum Kenotariatan, 2026)
The increasing use of digital wallets as a cashless payment method in Indonesia facilitates transactions but also raises legal issues, such as the disappearance of users’ balances without any transactions being made or authorized by the account holders. This phenomenon raises questions regarding the legal liability of app operators, the forms of legal protection available to users, and the effectiveness of existing dispute resolution mechanisms. This study aims to analyze the legal liability of the DANA app operator for user losses, examine legal protections for digital wallet users from a legal theory perspective, and analyze dispute resolution mechanisms for balance losses without transactions based on Indonesian positive law. This study employs a normative legal method using a statutory approach and a conceptual approach through the analysis of primary, secondary, and tertiary legal sources. The results indicate that the DANA app operator bears legal responsibility to ensure the security and reliability of the electronic system and to provide compensation if user losses are proven to be caused by system failure or the operator’s negligence. Legal protection for users has been normatively regulated through the ITE Law, the UUPK, and payment system regulations; however, its implementation has not been fully effective due to ongoing disparities in the burden of proof and the operator’s control over electronic data. This study offers a novel approach by integrating an analysis of the operator’s legal liability, legal protection based on the theories of Satjipto Rahardjo and Philipus M. Hadjon, and the effectiveness of dispute resolution mechanisms into a single study examining cases of lost user balances without any transactions. Thus, it is necessary to strengthen legal protection and dispute resolution mechanisms to ensure legal certainty and justice for digital wallet users.